2022
DOI: 10.3390/min12050631
|View full text |Cite
|
Sign up to set email alerts
|

Iron Ore Sinter Macro- and Micro-Structures, and Their Relationships to Breakage Characteristics

Abstract: A systematic analysis of industrial iron ore sinter product and associated sinter returns was undertaken. The samples were characterised through identification of the major macro- and micro-structural types present in these materials. Examination of the breakage surfaces of the particles indicates a strong correlation between mechanical sinter strength and sinter microstructure. Preferential breakage was observed to occur in sinter materials having high porosity and those microstructures consisting of isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The mineral species, content, and morphological pairs of sintered ores are closely related to the structural characteristics of the mineral phases [11]. Cheng et al [12] classified the sintered ore phase into four mineral phase structures based on the microscopic mineral composition and mineral morphology and analyzed the causes of the different mineral phase structures and their effects on the mechanical strength of sintered ores. The results showed that the power of the sintered ores depended on the mineral phase structures present in the microscope and the distribution of these microscopic structures.…”
Section: Introductionmentioning
confidence: 99%
“…The mineral species, content, and morphological pairs of sintered ores are closely related to the structural characteristics of the mineral phases [11]. Cheng et al [12] classified the sintered ore phase into four mineral phase structures based on the microscopic mineral composition and mineral morphology and analyzed the causes of the different mineral phase structures and their effects on the mechanical strength of sintered ores. The results showed that the power of the sintered ores depended on the mineral phase structures present in the microscope and the distribution of these microscopic structures.…”
Section: Introductionmentioning
confidence: 99%